The Effect of Midwife Education on MPASI Containing Prebiotics on Maternal Compliance in Giving MPASI - Titi Purwitasari Handayani; Resty Noflidaputri (Bulletin of Inspiring Developments and Achievements in Midwifery, 2026)
Timely, adequate, and quality complementary feeding (MPASI) is important to support infant growth and development. However, limited maternal knowledge and insufficient education from health workers, especially midwives, often lead to inappropriate feeding practices. Therefore, educational interventions are needed to improve maternal understanding and compliance with complementary feeding recommendations. This study aimed to determine the effect of midwife-led education on maternal compliance in providing complementary feeding containing prebiotics. This study used a quantitative quasi-experimental design with a pretest–posttest control group approach. The research was conducted in the working area of the Mining Health Center, Kampar Regency, Riau Province. A total of 60 mothers with infants aged 6–12 months were selected using purposive sampling and divided into intervention and control groups, each consisting of 30 participants. The intervention included counseling sessions, leaflets, and interactive discussions about prebiotic-containing complementary feeding. Data were collected using a validated compliance questionnaire. The results showed that before the intervention, most mothers in the intervention group had low compliance (66.7%). After the intervention, high compliance increased to 73.3%, while the control group showed lower compliance (36.7%). Chi-square analysis showed a significant effect of midwife education on maternal compliance (p=0.002). These findings indicate that midwife-led education effectively improves maternal compliance in providing appropriate complementary feeding containing prebiotics.